Impact of age on the comparison between short-term vs 12-month dual antiplatelet therapy in patients with acute coronary syndrome treated with the COMBO dual therapy stent: 2-Year follow-up results of the REDUCE trial. (March 2021) - Kedhi, Elvin; Verdoia, Monica; Suryapranata, Harry; Damen, Sander; Camaro, Cyril; Benit, Edouard; Barbieri, Lucia; Rasoul, Saman; Liew, Houng B.; Polad, Jawed; Ahmad, Wan AW.; Zambahari, Robaayah; et al.
Abstract: Background and aims: The impact of advanced age on the optimal duration of dual antiplatelet therapy (DAPT) in patients with acute coronary syndrome (ACS) undergoing percutaneous coronary revascularization (PCI) is still greatly debated. Therefore, the aim of the present sub-analysis of the REDUCE trial was to assess the impact of age on the comparison between a short 3 months vs standard 12 months DAPT in ACS patients treated with the COMBO Dual Stent Therapy. Methods: The REDUCE trial is a prospective, multicenter, investigator-initiated study that randomized ACS patients undergoing PCI with the COMBO drug eluting stent to either 3 or 12 months of DAPT. The study population was divided according to age (<or ≥ 75 years). Primary study endpoint was a composite of all-cause mortality, myocardial infarction, definite/probable stent thrombosis (ST), stroke, target-vessel revascularization (TVR) and bleeding (BARC II, III, V) at 12 months. Secondary endpoints were cardiovascular mortality and the individual components of the primary endpoint within 24 months. Results: From June 2014 to May 2016, 1496 patients were included in the study, of whom 205 (13.7%) ≥75 years of age. Among them, 50.7% of the elderly and 50.2% of younger patients were assigned to the 3-month DAPT treatment. Baseline characteristics were well matched between the two arms, except for a higher rate of males ( p= 0.02) and a reduced number of lesions on the right coronary artery ( p= 0.02) in elderly patients treated for the short DAPT duration. Median follow-up was 682.5 days [IQR:667-731]. At 12 months, no difference in the primary endpoint was observed according to DAPT duration in both patients aged ≥75 years (22.1% vs 18.8%, HR [95%CI] = 1.6 [0.73–3.5], p= 0.24) and younger ones (9.7% vs 10.9%, HR [95%CI] = 0.85 [0.59–1.27], p= 0.44; p INT = 0.15). Results were confirmed after correction for baseline differences among the elderly (adjusted HR [95%CI] = 1.7 [0.75–3.9], p= 0.21). Comparable rates of survival, thrombotic (MI, stent thrombosis, TVR, stroke) and bleeding events were observed with the two DAPT strategies, with no impact of age. Conclusions: The present study shows that among ACS patients randomized in the REDUCE trial, a 3-month DAPT strategy was comparable to a standard 12-month DAPT at a 2-year follow-up for both ischemic and bleeding endpoints, in elderly and younger patients. Thus, despite presenting the limitations of a subgroup analysis, our study strengthens the feasibility of a shorter DAPT duration even among high-risk subsets of ACS patients. Graphical abstract: Image 1 Highlights: Advanced age enhances the bleeding risk associated with dual antiplatelet therapy. The optimal duration of dual antiplatelet therapy in elderly patients with acute coronary syndromes (ACS) is debated. The REDUCE trial compared 3 vs 12 months DAPT in ACS patients treated with the COMBO Dual Stent Therapy. We provide a sub-analysis of the REDUCE trial according to age. No age-related difference was observed in the primary composite or individual thrombotic and bleeding endpoints at 12 months.